2004
DOI: 10.1097/01.mcd.0000127469.49759.10
|View full text |Cite
|
Sign up to set email alerts
|

Scalp lesions in Turner syndrome: a result of lymphoedema?

Abstract: Lymphoedema and skin naevi are common in children with Turner syndrome (TS). Lymphoedema in the early stages of fetal life is thought to cause several of the phenotypic characteristics in patients with TS such as nuchal folds and pterygium colli. We present two patients with TS who have unusual lesions on the scalp. The first patient had an oval circumscribed lesion. Two biopsies were obtained from the lesion. Increased numbers of collagen fibres were seen in the reticular dermis suggesting the diagnosis of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Clinical practice suggests that keloids commonly occur, but one report showed that only about 3% developed keloids or hypertrophic scars after surgical procedures (402). Prevalence data are not available for alopecia areata (23, 400, 403) and for cutis verticis gyrata (402,404,405,406) though case reports exist. Whorling skin pigmentation patterns, such as hypomelanosis of Ito, may accompany mosaic karyotypes (407).…”
Section: Dermatologymentioning
confidence: 99%
“…Clinical practice suggests that keloids commonly occur, but one report showed that only about 3% developed keloids or hypertrophic scars after surgical procedures (402). Prevalence data are not available for alopecia areata (23, 400, 403) and for cutis verticis gyrata (402,404,405,406) though case reports exist. Whorling skin pigmentation patterns, such as hypomelanosis of Ito, may accompany mosaic karyotypes (407).…”
Section: Dermatologymentioning
confidence: 99%
“…reported two cases of scalp collagen nevi associated with Turner syndrome and considered it as resolving stage of lymphoedema. [3] In a study by Laxmisha et al . described isolated scalp collagenoma mimicking cutis verticis gyrata in a 35-year-old female with no associated abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Growth/Stature At birth, infants with TS will typically fall within the lower end of the normal range for length. As they continue to grow, their growth velocity tends to decrease so that a diagnosis may be made by 18 months, or their growth failure may be so mild that the child will go undetected until midchildhood or puberty (when it becomes obvious that a girl with TS is not going to maintain her pubertal growth spurt).…”
Section: Lymphatic Systemmentioning
confidence: 99%
“…Unfortunately, because the cystic hygromas and lymphedema are present during development, females with TS may be left with a webbed neck, scalp lesions, concave, hyperconvex, or upturned fingernails, a transverse palmar crease, or several other dermatologic anomalies. 22,23 Growth/Stature At birth, infants with TS will typically fall within the lower end of the normal range for length. As they continue to grow, their growth velocity tends to decrease so that a diagnosis may be made by 18 months, or their growth failure may be so mild that the child will go undetected until midchildhood or puberty (when it becomes obvious that a girl with TS is not going to maintain her pubertal growth spurt).…”
Section: Lymphatic Systemmentioning
confidence: 99%